2022
DOI: 10.7575/aiac.ijkss.v.10n.1p.30
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Walking Exercise on Blood Pressure and Blood Glucose in the Elderly

Abstract: Background: Walking exercise is a physical activity that stimulates various components of physical fitness. Particularly in the elderly, it improves blood circulation, strengthens bones, lowers blood pressure and glucose. Objective: This study aimed to determine the effect of walking exercise on blood pressure and blood glucose in the elderly. Method: This research was experimental research that used a quantitative approach. Participants were elderly aged 60 years with a history of hypertension and high blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…As can be seen, our results bring new knowledge to an area that needs to be investigated for health reasons. In fact, recently in an experimental study, they observed that walking had a significant effect on blood pressure and blood glucose [45]. Similarly, after physical training in a case of poststroke dementia, improvements were observed in regaining strength, cognitive function, attention, and memory [46], and even against sarcopenia as a disorder of aging associated with many musculoskeletal and nervous system problems, attenuating muscle reduction, improving body instability, falls and injuries, so active activities and active lifestyles can delay the process and avoid instability due to lack of muscle, lack of coordination and injuries [47].…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen, our results bring new knowledge to an area that needs to be investigated for health reasons. In fact, recently in an experimental study, they observed that walking had a significant effect on blood pressure and blood glucose [45]. Similarly, after physical training in a case of poststroke dementia, improvements were observed in regaining strength, cognitive function, attention, and memory [46], and even against sarcopenia as a disorder of aging associated with many musculoskeletal and nervous system problems, attenuating muscle reduction, improving body instability, falls and injuries, so active activities and active lifestyles can delay the process and avoid instability due to lack of muscle, lack of coordination and injuries [47].…”
Section: Discussionmentioning
confidence: 99%
“…Guidance on engagement in optimal physical activity behavior may be beneficial for persons with type 2 diabetes. Conversely, walking, a form of physical activity that is classified as economical and has a low risk [ 29 ] may be easier and more realistic and achievable for persons with type 2 diabetes to engage in, compared to vigorous forms of physical activity. The study findings that walking was associated with improved quality of life thus suggest that persons with diabetes may benefit from interventions incorporating walking.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring blood pressure regularly is essential in detecting and preventing health complications such as hypertension [19], [20], [24], [27], [35]. For patients with hypertension, daily blood pressure measurements are key to monitoring the effectiveness of treatment, including drug dose adjustments.…”
Section: Introductionmentioning
confidence: 99%